INFLASI, NILAI KURS, BI RATE, LEVERAGE RATIO DAN PENGARUHNYA TERHADAP RETURN SAHAM - Novi, Ria; Mufida, Vita Ilma (COMPETITIVE, 2024)
The economic conditions of a country and company have a significant influence on the size of stock returns. This fact shows that there are fluctuations in stock returns which experience rapid increases and decreases. This research aims to analyze the influence of inflation, exchange rate, Bl rate, and leverage ratio on stock returns in companies listed on the Jakarta Islamic Index for the 2021-2023 period. The sampling method used in this research is the purposive sampling method. There are 19 companies in the time period 3 years so there are 57 samples. The analysis method for this research uses classical assumption tests and multiple linear regression analysis using SPSS software. The results of this research show that partially the inflation variable has a negative and significant effect on stock returns, the wala kars and BI rate variables have a positive and significant effect on stock returns, while the debt to equity ratio has a negative and insignificant effect on stock returns. Simultaneously, the variables inflation, exchange rate, BI rate, and DER have a significant effect on stock return.